2014
DOI: 10.1586/14760584.2014.924405
|View full text |Cite
|
Sign up to set email alerts
|

Could moderate alcohol intake be recommended to improve vaccine responses?

Abstract: Summary The impacts of alcohol consumption on human health are complex and modulated by several factors such as patterns and amounts of drinking, genetics, the organ system studied, as well as the sex and the age of the user. There is strong evidence that chronic ethanol abuse is associated with increased morbidity and mortality, immunosuppression, and increased susceptibility to both bacterial and viral infections. In contrast, moderate alcohol consumption exerts positive effects including decreased mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
0
10
2
Order By: Relevance
“…The impacts of alcohol consumption on health are complex and modulated by several factors such as pattern and amount of drinking, genetics, the organ system studied, and the sex and age of the user27. Regular heavy consumption (≥3 drinks a day in men) causes suppression of innate immunity28, whereas moderate consumption (<2 drinks a day for men)29 may enhance the effects of vaccines27 and increase intestinal permeability30, which can lead to immune recognition of self-antigens31. Here, the effects of alcohol were not considered beneficial, since autoantibodies can mark future autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…The impacts of alcohol consumption on health are complex and modulated by several factors such as pattern and amount of drinking, genetics, the organ system studied, and the sex and age of the user27. Regular heavy consumption (≥3 drinks a day in men) causes suppression of innate immunity28, whereas moderate consumption (<2 drinks a day for men)29 may enhance the effects of vaccines27 and increase intestinal permeability30, which can lead to immune recognition of self-antigens31. Here, the effects of alcohol were not considered beneficial, since autoantibodies can mark future autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…In two studies, we found that those who abstain from consuming alcohol are at greater risk for colds than those who drink one to four drinks a day. Because we did not have heavier drinkers in our studies, we cannot conclude anything about the potential effects of consuming greater doses, although the evidence on alcohol abuse and immunity leads us to expect that greater numbers of drinks would be associated with greater risk (Barr et al, 2016; Messaoudi, Pasala, & Grant, 2014). A recent British study of risk for COVID-19 hospitalization similarly found greater risk among those who were nondrinkers before virus exposure but only weak evidence for an increase in risk for those who were heavier drinkers (Hamer, Kivimakib, Gale, & Batty, 2020).…”
Section: Risky Behaviors and Disease Susceptibilitymentioning
confidence: 94%
“…We have leveraged this model to define the impact of chronic drinking on circulating and tissue resident immune cells 4146 . Specifically, using this model, we have shown that CMD enhances while CHD attenuates vaccine responses 42,44,47 . More recently, we reported significant transcriptional changes in PBMC from female rhesus macaque following 12 months of CHD using RNA-Seq and concluded that the circulating innate immune cells bear the largest burden of chronic heavy drinking 46 .…”
Section: Introductionmentioning
confidence: 99%